1998
DOI: 10.1515/bchm.1998.379.2.219
|View full text |Cite
|
Sign up to set email alerts
|

Sorting of Non-Glycosylated Human Procathepsin S in Mammalian Cells

Abstract: Cathepsin S, a lysosomal cysteine protease, is synthesized as inactive precursor. It is activated in the lysosomes by a proteolytic cleavage of the propeptide. HEK 293-cells which do not express cathepsin S were transfected with cDNA of either wild type human procathepsin S or a mutant procathepsin S in which Asn of the only glycosylation site in the proregion was replaced by Gln. The cells expressed glycosylated and non-glycosylated procathepsin S, respectively. Large amounts of the precursors were secreted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 21 publications
0
32
0
1
Order By: Relevance
“…The importance of glycosylation and its associated mannose-6-phosphate pathway on the cellular maturation of cathepsins B, L and S has already been observed in various studies using inhibitors or mutagenesis approaches (25)(26)(27). When the cathepsin K-expressing cells were incubated with tunicamycin, a strong inhibition of enzyme maturation and secretion of the proenzyme was detected, indicating that both processes require glycosylation.…”
Section: Discussionmentioning
confidence: 76%
“…The importance of glycosylation and its associated mannose-6-phosphate pathway on the cellular maturation of cathepsins B, L and S has already been observed in various studies using inhibitors or mutagenesis approaches (25)(26)(27). When the cathepsin K-expressing cells were incubated with tunicamycin, a strong inhibition of enzyme maturation and secretion of the proenzyme was detected, indicating that both processes require glycosylation.…”
Section: Discussionmentioning
confidence: 76%
“…The 293 cells (3 3 10 6 ) were transiently cotransfected with HLA-DRA*0101, HLA-DRB1*0101, CD54::GPI, CD80::GPI, CD86::GPI, CD58::GPI, cathepsin S, 19 Ii constructs, minigenes, GFP control vector, or empty control vector (30 mg DNA) by the calcium phosphate precipitation method in combinations as indicated and used 72 hours after transfection. VLP induction was achieved by cotransfection of MoMLV gag/pol.…”
Section: Generation Of Antigen-presenting 293 Cells and Vlpsmentioning
confidence: 99%
“…Generation of invariant chain constructs pcDNA1.1/Amp containing an invariant chain (Ii) with a SfuI-Eco47III cassette instead of class II-associated Ii peptide (CLIP) was kindly provided by J. vanBergen (Immunohematology and Blood Transfusion, Leiden, The Netherlands). 24 The double-stranded Art v 1 [25][26][27][28][29][30][31][32][33][34] oligonucleotides Art v 1 [25][26][27][28][29][30][31][32][33][34] upper 59-CGAAGTGCATCGAGTGGGAGAAGGCCCAGCACCAGGC-39 and Art v 1 [25][26][27][28][29][30][31][32][33][34] lower 59-GCCTGGTGCTGGGCCTTCTCCCACTCG ATGCACTT-39 were inserted into SfuI/Eco47III-digested pcDNA1.1/AmpIi. CLIP and HA 309-317 containing Iis were constructed as previously described.…”
Section: Cell Lines and Primary Cellsmentioning
confidence: 99%
“…20 More than 95% of patients with mugwort allergy are sensitized to Art v 1, the major allergen in mugwort pollen. Analyzing the T-cell response to Art v 1 by using a panel of specific T-cell lines and clones revealed that the presentation of the sole immunodominant epitope (Art v 1 [25][26][27][28][29][30][31][32][33][34][35][36] ) is highly associated with HLA-DRB1*01. 21,22 Thus allergy to Art v 1 is characterized by a uniform T-cell response.…”
mentioning
confidence: 99%